Model pembelajaran complete sentence untuk meningkatkan keterampilan menulis karangan narasi - Nidya Ayu Oktavia; Sukarno Sukarno; Chumdari Chumdari (Universitas Sebelas Maret, 2020)
This research aimed to explain narrative writing skills by applying a Complete Sentence learning model. A Classroom Action Research is used as the form of this research, conducted for two cycles. The stages of the cycle are planning, implementation, observation, and reflection. The subjects of this research were students of the A fourth-grade at Dukuhan Kerten No. 58 Public Elementary School in the 2019/2020 academic year, totaling 27 students. These data collection techniques in the research are interviews, observation, tests, and documentation. The data validities is content validity and triangulation. The analysis of the data are statistic descriptive and interactive analysis. The result of the research showed that using a Complete Sentence learning model can improve narrative writing skills. The first cycle resulting in a percentage of 44.44 in classical. The second cycle with a percentage of 77.78 in classical terms. The conclusion of this research is the narrative writing skills of A fourth-grade students of Public Elementary School Dukuhan Kerten No. 58 academic year 2019/2020 increases through the application of Complete Sentence learning models.